Evaluation of the impact on quality of life of patients with temporomandibular disorders - Carolina Almeida Rodrigues; Lais Valencise Magri; Melissa de Oliveira Melchior; Marcelo Oliveira Mazzetto (Revista Dor)
ABSTRACTBACKGROUND AND OBJECTIVES:Chronic pain, such as temporomandibular disorder, often leads to significant changes in quality of life. This study aimed at evaluating the influence of temporomandibular disorders in the subjective perception of quality of life by means of the Oral Health Impact Profile-14.METHODS:Participated in the study 80 patients diagnosed with temporomandibular disorders by means of the Research Diagnostic Criteria for Temporomandibular Disorders, aged between 18 and 60 years (32.71±1.1), who were submitted to the Oral Health Impact Profile-14 questionnaire. Non parametric Mann-Whitney statistics, Pearson Correlation test, Analysis of Variance and Tukey test were used with significance level of 5%.RESULTS:There has been no statistically significant difference in the perception of the impact on quality of life between genders; patients with association of signs and symptoms of the three groups of the Research Diagnostic Criteria for Temporomandibular Disorders had further impact on quality of life, as well as the most severe the temporomandibular disorder the highest the reported impact (p=0.05), and the age group with the highest impact on quality of life was between 18 and 30 years (p<0.01).CONCLUSION:Increased age, severity and the association of diagnoses have exacerbated the impact of temporomandibular disorders on quality of life. Variables analyzed in this study were related to temporomandibular disorder chronicity, stressing the importance of early intervention strategies to minimize the impact on quality of life.